PKM Optimizes Legal Protection of The Copyright of Woven Fabric Craftsman Desa Adat Tenganan Dauh Tukad, Kecamatan Manggis,Kabupaten Karangasem - I Made Minggu Widyantara; I Gusti Agung Ayu Gita Pritayanti Dinar; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Community Service Journal of Law, 2024)
A copyrighted work will receive legal protection covering the fields of science, art and literature. Legal protection is obtained if a creation has been realized in a tangible form. It is interesting to observe that the dynamic nature of copyright itself has been contextually confirmed in Article 40 paragraph (1) of Law Number 28 of 2014 concerning Copyright. Traditional fabrics with natural motifs such as those in Tenganan Dauh Tukad Village. Tenganan Dauh Tukad Village is a village that neighbors the Bali Aga Tenganan Village which is very famous in the world because of its unique culture and traditional woven fabrics with natural motifs and using natural materials. In contrast to Tenganan Pengringsingan Village, which is very famous for its world-famous weaving crafts, the crafts produced by craftsmen in Tenganan Dauh Tukad Village are not as well-known as the craftsmen of Tenganan Pengringsingan Village. In Tenganan Dauh Tukad Village there are groups of craftsmen who advertise handicrafts and weaving with motifs adapted to market demand and crafts according to the initiative and creations of the craftsmen. Most of the craftsmen who produce craft motifs in Tenganan Dauh Tukad Village have not registered the copyright for the work or designs produced by the craftsmen.